Properties of ((CH3NH3)1-xCsx)3Bi2I9: (x=0-1.0) Hybrid Perovskite Solar Cells with Chlorobenzene Treatment (Journal of Solar Energy Research Updates, 2024)
Abstract: Hybrid-perovskite solar cells, a promising lead-free perovskite material, have been attracted for optoelectronic applications due to an excellent optical and electrical properties with low production cost. Herein, methylammonium bismuth iodide and cesium bismuth iodide were mixed to form hybrid structure for the improvement of photovoltaic properties, which were fabricated using all-solution processed multi-step spin coating technique with changing the composition, x, of CBI, ((CH3NH3)1-xCsx)3Bi2I9; (x=0 – 1.0). Chlorobenzene was added to the solution to improve the surface morphology. By optimizing the composition of CBI in MBI, the morphology, structural and optical properties of HPeSCs have been improved. It showed that the morphology is homogeneous, compact and a uniform layer, while the crystallinity shows an improvement as well. The open circuit voltage, the short circuit current and the power conversion efficiency were much improved with using hybrid structure. Our study shows that the significance of the hybridization process gives a new route in fabricating a better active absorber layer of PeSCs in the future.